Integration of Constraint Programming, Artificial Intelligence, and Operations Research : 16th International Conference, CPAIOR 2019, Thessaloniki, Greece, June 4-7, 2019 : Proceedings /: 16th International Conference, CPAIOR 2019, Thessaloniki, Greece, June 4-7, 2019 : Proceedings. (2020) - Unknown
No abstract available